Analysis of Bird Vocal Bandwidth in Relation to Vegetation Structure Variability in Coffee Agroforestry Systems, Jember, Indonesia - Kurnianto, Agung Sih; Dewi, Nilasari; Haryadi, Nanang Tri; Khowatini, Husnul; Lestari, Ayu; Lestari, Auralia Sakinah; Efendi, Galang Prasetyo; Hanafi, Ahmad Rifqi A.; Kadafi, Ahmad Muammar (HAYATI Journal of Biosciences, 2025)
Bird vocalizations are crucial for communication and adaptation to environmental changes. As forests are converted to agriculture, agroforestry plays a key role in conserving biodiversity. This study examines vocal bandwidth variations in four bird species-Common Tailorbird (Orthotomus sutorius), Sooty-headed Bulbul (Pycnonotus aurigaster), Olive-backed Sunbird (Cinnyris jugularis), and Small Minivet (Pericrocotus cinnamomeus)-across three coffee agroforestry sites in Jember, Indonesia: Silo, Kluncing, and Kaliwining. The study explores how vegetation structure influences vocal adaptations using sound recordings, vegetation surveys, the Kruskal-Wallis test, and Pearson correlation analysis. Results show significant vocal bandwidth differences in Common Tailorbird and Sooty-headed Bulbul. Common Tailorbird exhibited the highest bandwidth variation in Silo (2.85 kHz), followed by Kluncing (2.30 kHz) and Kaliwining (1.10 kHz) (p